A Critical Discourse Analysis of the Representation Of Islam and Muslims Following the 9/11 Events As Reported in the New York Times - Alazzany, Murad Ali Obaid Abdullah (2008)
This study aims to examine and elucidate on how Islam and Muslims are portrayed and represented in the discourses reported in the New York Times (NYT) newspaper in the wake of the September 11 events and in the ensuing two years. The focus of this study was to provide empirical evidence to substantiate claims relating to the representation of Islam and Muslims and in response to these events. Within this focus, the system of representation is grounded in the multi-disciplinary approach of Critical Discourse Analysis (see Fowler, 1991; Fairclough, 1995). The former is the Critical linguistic approach and the latter, the Textual Analysis approach. Together the CDA approach is adopted to reveal the ideological themes imbriacted in the language of the NYT. These ideological themes are assumed within this multi-disciplinary approach to be promoted through certain linguistic structures and discursive strategic practices. The data of this study is collected from Thomson Gale's Pro Quest Newsstand which is affiliated to the British council library in Malaysia. Within the Thomson Gale Data Base, the terms 'Islam' and 'Muslim' were keyed in and searched in two separated processes. Choosing the full text option and entering the specific data ring from September 2001 to September 2003, Thomson Gale Newsstand displayed a total number of 1814 articles. This number of articles was refined further by eliminating editorials, letters to the editor, and those articles whose primary concern had no relevance to the main aims of the study. Thus, the number of these articles was reduced into 450 articles. However, a closer inspection revealed that the focus of many of the left articles did not fit into the logical categorization of this thesis. In addition, a critical reading of the data revealed that certain themes and topics were covered frequently and repetitively in many articles throughout the data. Thus, once the articles were examined and refined more critically, their number was systematically reduced to 78. In the light of the theoretical and methodical approaches of this study, the analysis of the discourses in the NYT showed that most of the themes that dominate the representational discourse of Islam and Muslims hover around the concepts of violence, turmoil, threat, jihad, and evilness of Islam and Muslims. It is also revealed that the NYT utilizes some discursive strategies like generalization and selection to promote these ideological themes that are manifested in the representational discourse of Islam and Muslims. In addition, it is found that these themes are reinforced by linguistic tools like transitivity, nominalization and the choice of some lexical items. However, the examination of the whole representational discourse of Islam and Muslims reveals that it would be a distortion to claim that the representation of Islam and Muslims merely hovers around the themes mentioned. In fact, it is found that the representation of Islam and Muslims took a new shift as the NYT creates a thematic dichotomy of two levels of the subjects under analysis. On one level, it creates a dichotomy between moderate Islam and Muslims and extremist Islam and Muslims. On another level, it creates a dichotomy between external and internal Muslims. This dichotomy is the matized and consolidated through the same linguistic structures mentioned above and other discursive strategies. The discursive strategies that are utilized by the NYT to reinforce this thematic dichotomy are classification and essentialization. The differentiation strategy provides the NYT with great flexibility both to denigrate the enemy, as embodied by extremism and external Muslims, and at the same time, to praise moderate and internal Muslims. From another perspective, the NYT utilizes the essentialization strategy to represent any Muslim who operates in Islamic politics as an extremist. In addition, it lumps all Islamic movements together, portraying them as a threat without concern as to whether they are traditional, modern, violent or peaceful. In adopting this strategy, it thus becomes unclear where moderate Islam ends and where extremism or fundamentalism begins. On the whole, this study has shown that there are several ideological themes that are embodied in the representation of Islam and Muslims in the NYT. These ideological themes are projected through various discursive strategies and linguistic structures. Such findings confirm that our theoretical lines that are based on Fowler's (1991) and Fairclough's (1995) view that language reproduces ideology and hence every thing that is reported in the press is reported from an ideological point of view.